Mg2+–W6+ co-doped Li2ZnTi3O8 anode with outstanding room, high and low temperature electrochemical performance for lithium-ion batteries. Issue 11 (8th October 2019) - Shen, Ziye; Zhang, Zhongxue; Wang, Song; Liu, Zenan; Wang, Lijuan; Bi, Yanfeng; Meng, Zhaohui
Abstract : LM6ZTW3O co-doped with Mg 2+ –W 6+ with excellent low temperature electrochemical performance has been synthesized using a simple solid-state method. Abstract : Li2 ZnTi3 O8 (LZTO) co-doped with Mg 2+ –W 6+ (LM6ZTW3O) has been successfully prepared by a facile one-step solid-state route. A co-doping strategy improves ionic conductivity, reduces transfer resistance, internal resistance and polarization, stabilizes the structure of LZTO and enables the LM6ZTW3O electrode to have a good electrical contact. The co-doped LZTO exhibits excellent electrochemical performance at room, high and low temperatures. At 1 A g −1, 94.7% of the capacity for the 2nd cycle is kept at room temperature after 400 cycles. At 2 A g −1, there is no capacity decay at the 300th cycle at room temperature. Even at 3 A g −1, 177.9 mA h g −1 is kept at the 120th cycle. At 55 °C, 88.3% of the capacity for the 2nd cycle is obtained at 1 A g −1 . At 0 °C, 192.9 mA h g −1 is still obtained at 0.6 A g −1 for the 60th cycle, and there is no capacity decay for 200 and 300 cycles at 0.2 and 0.5 A g −1, respectively.